Venom as therapeutic weapon to combat dreadful diseases of 21st century: A systematic review on cancer, TB, and HIV/AIDS - Khusro, Ameer (2018)
Cancer and infectious diseases are the preeminent causes of human morbidities and mortalities worldwide. At present, chemotherapy, radiotherapy, immunotherapy, and gene therapy are considered as predominant options in order to treat cancer. But these therapies provide inadequate consequences by affecting both the normal and tumor cells. On the other hand, tuberculosis (TB), and HIV (human immunodeficiency virus) infections are significant threats, causing over a million mortalities each year. The extensive applications of antibiotics have caused the microbes to acquire resistance to the existing antibiotics. With the emerging dilemma of drug resistant microbes, it has become imperative to identify novel therapeutic agents from natural sources as emphatic alternative approach. Over the past few decades, venoms derived from several reptiles, amphibians, and arthropods including snakes, scorpions, frogs, spiders, honey bees, wasps, beetles, caterpillars, ants, centipedes, and sponges have been identified as efficient therapeutics. Venoms constitute plethora of bioactive components, particularly peptides, enzymes, and other chemical entities, which exhibit a large array of anticancer and antipathogenic activities. This review highlights the panorama of bioactive components of animal venoms divulging the anticancer, anti-tubercular, and anti-HIV activities. In a nutshell, this context discloses the decisive role of animal venoms as alternative natural resources to combat these deadly diseases of 21st century, and propounding the plausible development of new therapeutic drugs in the present era.